Consumption pattern of dairy products in Sabah, Malaysia during Covid-19. Issue 1 (1st November 2022) - Seriger, N S S B M J; Rahman, M M; Umami, N; Mat, K; Nor, M M; Rosli, N D; Khalif, R I A B R
Abstract : Dairy production has a considerable effect on climate change due to emissions of greenhouse gases, but dairy products are meals that are well-known for their pleasant taste and nutritional value. During the Covid-19 outbreak, there were shortages of dairy goods on the shelves of grocery stores. This study investigated the consumption patterns of dairy products in Sabah. Using a pre-tested questionnaire, data were collected through online survey during Covid-19 outbreaks from 64 households comprising 16 from rural, 25 from town and 23 from city areas. The surveyed households were classified into 5 groups based on monthly household income: (i) ≤RM2000, (ii) RM2001-RM3000, (iii) RM3001-RM4000 and (iv) >RM4000. Among the participated households, 75% of respondents were female and 25% were male. There was a significant relationship among household income groups for fresh milk consumption. Regardless of areas and household incomes, the average monthly consumption for evaporated milk, fresh milk, condensed milk, powder milk, sweetmeats, yogurt, butter and ice cream per household were 1018g, 1425ml, 978g, 815g, 527g, 468g, 522g, and 650g, respectively. 28% of respondents monthly consumed 0.5-1.0 L fresh milk per household. 42%, 39%, 39%, 63%, 58%, 64% and 50% of respondents-- respectively-- monthly consumed evaporated milk, condensed milk, powder milk, sweetmeats, yogurt, butter and ice cream, where the amount of each component was not more than 500g per household. Results showed that 38% of respondents liked more on butter followed by cheese (30%), yogurt (20%), cream (9%) and condensed milk (3%). The 25% and 45% of respondents had reduced their consumption and expenditure behaviour, respectively. Results indicated that individual of city areas consumed more dairy products. Although cows add methane to our environment, organic dairy farming and husbandry methods can significantly reduce greenhouse gas emission.